EMPLOYEE PERFORMANCE ANALYSIS; POST MUTATIONS IMPLEMENTATION AT PT. JASA RAHARJA SURABAYA REPRESENTATIVE - Anisa Dita Priutami; Leonard Adrie Manafe; Anita Kartika Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The aim of research to analyzing employee performance post the employee mutations implementation at PT. Jasa Raharja Surabaya Representative (JRSR). The descriptive qualitative method used in this study, using 5 (five) appropriate informants and supported by research articles and scientific documents. Data collection techniques by observation, interviews and documentation. The research results show that JRSR has implemented the mutation program well. The mutations implementation is carried out by Versatility Transfer (VT) means transferring employees by transferring positions aimed to increasing the capabilities and career employees development. Production Transfer (PT), which means transferring employees with the same or different positions but in different places. Employee performance at JRSR has been well and productive. It could be seen from the employees working hours, the work timeliness on and tasks completion and adjustments to new places and tasks shown well.